Sustainability Disclosure as a Mediation between Green Accounting and Corporate Performance - Pebriani, Reny Aziatul; Hendarmin, RM Rum; Lestari Setia Ningrum, Ayu (Jurnal Ilmiah Ekonomi Global Masa Kini, 2025)
This study examines the effect of green accounting on company performance, considering sustainability disclosure as a mediating variable. Green accounting practices refer to companies' efforts to integrate environmental aspects into financial reporting systems and strategic decision-making processes. However, previous studies have shown mixed results regarding the direct effect of green accounting on company performance. Therefore, sustainability disclosure is considered important in strengthening this relationship because it communicates corporate responsibility to stakeholders. This study uses a quantitative approach with secondary data from the annual and sustainability reports of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The analysis technique is structural equation modeling (SEM) based on partial least squares (PLS). Green accounting variables are measured based on environmental cost, environmental investment, and energy efficiency indicators. Sustainability disclosure uses GRI (Global Reporting Initiative) standards, and company performance is measured using ROA (return on assets), ROE (return on equity), and company value (Tobin’s Q) indicators. The results indicate that green accounting significantly positively affects sustainability disclosure, which significantly mediates the relationship between green accounting and corporate performance. These findings suggest that sustainability disclosure can enhance the value of green accounting practices and positively impact overall performance. These findings have practical implications, suggesting that companies should improve the quality of their sustainability reports as part of their long-term business strategy. Keywords: Green Accounting, Sustainability Disclosure, Company Performance.